2008
DOI: 10.1021/cg8009755
|View full text |Cite
|
Sign up to set email alerts
|

Oriented Nucleation of β-Hematin Crystals Induced at Various Interfaces: Relevance to Hemozoin Formation

Abstract: The nucleation of malaria pigment (hemozoin) and β-hematin crystals (synthetic hemozoin) can be promoted by lipid molecules. To determine the orientation of β-hematin crystals nucleated by 1-myristoyl-glycerol (MMG) on the water surface, we undertook a grazing incidence synchrotron X-ray diffraction and X-ray reflectivity study. Our results indicate that premixed R-hematin with MMG yielded β-hematin nanocrystals oriented with the {100} face parallel to water surface, which we explain insofar that the spreading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
34
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 22 publications
7
34
0
Order By: Relevance
“…Extensive evidence points to involvement of acylglycerol lipids in the crystallization of hemozoin. This includes promotion of formation of the synthetic analogue of hemozoin, β-hematin, in acylglycerol suspensions (2) and at various lipid-solution interfaces (3)(4)(5), mass spectroscopic analysis of lipids adsorbed on hemozoin crystals isolated from infected RBCs (6), and transmission electron microscopy (TEM) of histologically stained thin sections (6,7). Within the parasite Plasmodium falciparum, hemozoin crystals are found prominently in the DV.…”
mentioning
confidence: 99%
“…Extensive evidence points to involvement of acylglycerol lipids in the crystallization of hemozoin. This includes promotion of formation of the synthetic analogue of hemozoin, β-hematin, in acylglycerol suspensions (2) and at various lipid-solution interfaces (3)(4)(5), mass spectroscopic analysis of lipids adsorbed on hemozoin crystals isolated from infected RBCs (6), and transmission electron microscopy (TEM) of histologically stained thin sections (6,7). Within the parasite Plasmodium falciparum, hemozoin crystals are found prominently in the DV.…”
mentioning
confidence: 99%
“…They demonstrated that the β-hematin crystallized at the water interface of spherical particles with a homogeneous (i.e., "solid") core, according to confocal microscopy (8). By comparison, β-hematin, grown in an O═SðCH 3 Þ 2 ∶CH 3 OH∶CH 3 Cl solution, in contact with a self-assembled HS─ðCH 2 Þ 11 OH monolayer exposing OH groups, was nucleated at the monolayer interface via its {100} face, whereas the monolayer, exposing a 1∶1 mixture of OH and CH 3 groups, promoted nucleation equally via {100} and {010} faces (7). Similar crystallization results were obtained by Wang et al in an acidic aqueous solution (9).…”
mentioning
confidence: 99%
“…The initial assumption was that since acetone and methanol are fully miscible with water and only a very small volume was used relative to the aqueous medium, the lipid would be left spread over the surface. However, when grazing incidence X-ray diffraction (GIXD) and specular X-ray reflection (XR) were used to examine the surface (Figure 5), only a monolayer of lipid was seen on the surface in the absence of Fe(III)PPIX (de Villiers et al, 2009). When Fe(III)PPIX was present, this layer was evidently disturbed to the extent that no diffraction was seen, or was absent altogether.…”
Section: -Haematin Formation At Solvent/water and Lipid/water Interfmentioning
confidence: 99%
“…With the discovery of the role of the aqueousorganic interface in the process it was suggested that the lipid environment would encourage dehydration of H 2 O-Fe(III)PPIX to form -haematin because of the strong propensity of water to partition out of the lipid environment and because hydrogenbonding and electrostatic interactions are likely to be stronger in the low dielectric medium where competition for hydrogen bonding is absent Pisciotta & Sullivan, 2008). More recently, it has been proposed that haemozoin is nucleated by lattice epitaxy at the lipid surface (Solomonov et al, 2007;Weissbuch & Leiserowitz, 2008;de Villiers et al, 2009). Although definitive evidence remains lacking, the idea is very appealing since it provides a logical explanation for the role of the interface and is consistent with the observation of crystals aligned with the SNLD surface.…”
Section: -Haematin Formation At Solvent/water and Lipid/water Interfmentioning
confidence: 99%
See 1 more Smart Citation